TEXT AUTHORIZATION IN THE DEVELOPMENT OF SHARIA ECONOMIC LAW IN INDONESIA: Study of the Fatwa of the National Sharia Council of the Indonesian Ulama Council - Imam Mustofa (Fakultas Syariah, 2022)
DSN-MUI fatwa is a reference for the sharia standardization in Islamic financial institutions. Fatwa not only refers to primary references (Quran and Sunnah) strengthened by jurisprudence, but also secondary references such as ulamas’ opinions. This study analyzes the fatwa used as a text-based religious authority by the fatwa institution. This is a literature review which qualitative data are from primary and secondary sources collected through documentation, by reading the fatwa on Islamic finance from 2000-2012. Meanwhile, secondary data are articles, books, or studies related to the authority of religious texts in the sharia economic law discovery and development. The content analysis method was applied. This study found that of the 122 fatwas compiled in the DSN-MUI fatwa book, there were 47 fatwas (38.5%), referring to the opinions of salaf and contemporary ulamas as the basis, or as arguments and legitimacy. Based on the findings and analysis, the religion’s legitimacy and authority are at least based on two main things, the agents forming authority and references forming authority. Issuance of fatwa in sharia economic development is an attempt to reproduce the text’s authority. This study affirms previous studies reinforcing MUI as the religious authority, particularly in sharia economics.Fatwa DSN-MUI menjadi rujukan standardisasi kesyariahan sebuah lembaga keuangan syariah. Fatwa tidak hanya merujuk pada referensi primer (Quran dan sunnah) yang diperkuat dengan kaidah fikih, tetapi juga pada referensi sekunder dari pendapat para ulama. Kajian ini bertujuan menganalisa fatwa yang dijadikan otoritas keagamaan yang bertumpu pada teks oleh lembaga fatwa. Penelitian ini merupakan kajian kepustakaan dengan pendekatan kualitatif bersumber dari sumber data primer dan sekunder. Pengumpulan data dilakukan dengan dokumentasi, yaitu membaca fatwa tentang keuangan Syariah tahun 2000-2012. Data sekunder yaitu artikel, buku atau kajian terkait otoritas teks agama dalam penemuan dan pengembangan hukum ekonomi syariah. Data dianalisis dengan metode analisis isi. Kajian ini menemukan, dari 122 fatwa dalam buku kumpulan fatwa DSN-MUI, terdapat 47 fatwa (38,5%) yang merujuk pendapat ulama salaf dan kontemporer sebagai landasan fatwa-fatwa tersebut, atau setidaknya sebagai argumen dan legitimasi. Penelitian menunjukkan bahwa legitimasi dan otoritas agama setidaknya bertumpu pada dua hal pokok yaitu agen pembentuk otoritas dan referensi pembentuk otoritas. Penerbitan fatwa dalam konteks pengembangan ekonomi syariah merupakan upaya mereproduksi otoritas teks. Kajian ini mengafirmasi kajian-kajian sebelumnya yang menyatakan penguatan MUI sebagai pemegang otoritas keagamaan, khususnya dalam bidang ekonomi syariah.